A Comparative Study on Working Housemaids and a Control Group - Gupta S; Mitra S; Chatterjee P (Wolters Kluwer Medknow Publications, 2005)
Objective : To study the health status of paid housemaids within the age range of 15-55 years and above, in the study area. To compare the health status, morbidity pattern and some health related factors like contraceptive practices, between the working and non-working women of the same age-range, neighbourhood and socio-economic status and to identify any difference if existing between the two groups. To find out whether there is any specific health risk for the working women, related to their economic activity. To provide recommendations for specific conditions as observed. Study design : Cross sectional study. Method : Interview, physical examination. Setting : Slum settlement adjacent to Hooghly Station area, West Bengal. Participants : Women in the slum area, working in different houses of the neighbourhood as housemaids, constitute the study group. Same number of nonworking women from the same slum area, of similar age-range and socio-economic conditions were taken as controls. Results : The women of both the study and the control group live in appalling condition in small earthen huts with thatched roof. There is a gross lack of clean drinking water and sanitary facilities, for both the groups. A high prevalence of anaemia was found among both the working and non-working women under study. The working women are consistently found to have higher number of children than the non-working women, which may be a reason for their economic activity. The working women are also found to have their first childbirth at a relatively later age. Regarding contraceptive practices, most of the working women are found to accept the permanent method, whereas the non-working women under study have mostly opted for the temporary methods, specially the contraceptive.